Strategies for the synthesis of hydroxamic acids - Ganeshpurkar A.; Kumar D.; Singh S.K. (My University, 2025)
Background: Hydroxamic acids are a major class of organic compounds. They have a wide variety of pharmacological actions in targeting cancers, cardiovascular diseases, HIV, Alzheimer’s disease, Malaria, Allergic diseases. Objective: The present review focuses on the chemistry of conventional and non-conventional routes for the synthesis of hydroxamic acids reported till date. Conclusion: The hydroxamic acids are conventionally synthesized via carboxylic acid and their acid chloride derivatives. However, some other functional groups i.e. aldehyde, amine, amide and alcohol can also be converted to hydroxamate with ease. The solid phase synthesis techniques are also gaining importance for the synthesis of hydroxamic acids and these pathways have opened a wide arena for the synthesis of diverse and complex hydroxamic acids. © 2018 Bentham Science Publishers.